2013
DOI: 10.1259/dmfr.20120265
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of MRI for odontogenic tumours

Abstract: Objectives: To evaluate the diagnostic value of MRI for odontogenic tumours. Materials and methods: 51 patients with odontogenic tumours were subjected to preoperative MRI examinations. For tumours with liquid components, i.e. ameloblastomas and keratocystic odontogenic tumours (KCOTs), the signal intensity (SI) uniformity of their cystic components (US) was calculated and then their US values were compared. For tumours with solid components that had been examined using dynamic contrast-enhanced MRI (DCE-MRI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
(55 reference statements)
1
37
0
1
Order By: Relevance
“…However even though destruction of the tumor structure during resection has so far precluded direct comparison between MRI appearance and histological tissue characterization, the presented data revealed strong evidence for the applicability of MRI for the delineation of different lesion types. Fujita et al recently described the diagnostic value of MRI for the differentiation of certain odontogenic tumors [21]. Although the results were promising, one limitation of MRI has been shown to be its relatively low diagnostic ability for the assessment of the course of filled root canals.…”
mentioning
confidence: 99%
“…However even though destruction of the tumor structure during resection has so far precluded direct comparison between MRI appearance and histological tissue characterization, the presented data revealed strong evidence for the applicability of MRI for the delineation of different lesion types. Fujita et al recently described the diagnostic value of MRI for the differentiation of certain odontogenic tumors [21]. Although the results were promising, one limitation of MRI has been shown to be its relatively low diagnostic ability for the assessment of the course of filled root canals.…”
mentioning
confidence: 99%
“…However, conventional panoramic radiographs or CT cannot reliably discriminate between odontogenic cysts, keratocystic odontogenic tumours, and ameloblastomas MRI can, however, help. 9 While some studies have reported on possible differentiation between ameloblastomas and keratocystic odontogenic tumours, [5][6][7][8] or between true cysts and simple bone cysts, 11 we know of little if any detailed work that has focused on discrimination between keratocystic odontogenic tumours and odontogenic cysts based on MRI. Relatively few reported cases reflect this, as none of the relevant studies has included more than 10 cases of each of keratocystic odontogenic tumours and odontogenic cysts.…”
Section: Discussionmentioning
confidence: 99%
“…1 technique that is becoming increasingly important in oral and maxillofacial surgery is magnetic resonance imaging (MRI), which has already been evaluated for differentiating between ameloblastomas and keratocystic odontogenic tumours. [5][6][7][8] While dynamic, contrast-enhanced MRI has the potential to show the density of microvessels as a marker of proliferative or inflammatory activity in tissue, it has also been shown to contribute little to the differential diagnosis of odontogenic tumours, except for odontogenic fibromas and myxomas. 7 Diffusion-weighted MRI may help to characterise the contents of odontogenic cysts and tumours, as pure cystic liquids would restrict free Brownian motion of water molecules to a lesser degree than matrix structures within a solid or partly solid tumour.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations